ZERO-FIELD NUCLEAR MAGNETIC RESONANCE FOR STUDY OF ANTIFERROMAGNETIC PROPERTIES OF FeF3 MATERIALS - Suwandi, G. R. F.; Khotimah, S. N.; Haryanto, F. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2016)
Nuclear Magnetic Resonance (NMR) has been used as a research tool in many fields. In this study, the magnetic properties, especially anti-ferromagnetic properties of FeF3 materials were investigated. Zero-field custom-built NMR method was used to investigate the anti-ferromagnetic properties in the materials. Experiments have been carried out by varying the sample temperatures from 8 K to 220 K. Ordinary spin echo pulse sequence 90â°RFâ€“Ï„â€“180â°RF were used. Using Fast Fourier Transform, the signals in NMR spectrum were analyzed and the peak showed the resonance frequency. The result showed that resonance frequencies decrease with increasing in temperature. The frequency of the spectrum was around 85.41 MHz in the zero-temperature limit, and this corresponds with Fe hyperfine field at zero-temperature limit was 2.14 T. The temperature dependence of the local magnetization does not fit T2 Blochâ€™s Law very well. Instead, it fits the exponential form having an energy gap in the dispersion relation of the spin wave. It is obtained from the result that FeF3 is antiferromagnetic materials with energy gap of 11.466 meV and anisotropy energy of 1.045 meV.Nuclear Magnetic Resonance (NMR) telah banyak digunakan sebagai â€œresearch toolâ€ pada berbagai bidang kajian di fisika. Pada studi ini, akan dilakukan eksperimen untuk menguji sifat magnetik, khususnya antiferromagnetik pada material FeF3. Telah dilakukan eksperimen dengan memvariasikan temperatur pada sampel dari 8 K hingga 220 K. Pulse sequence yang digunakan adalah 90â°RFâ€“Ï„â€“180â°RF. Dengan memanfaatkan Fast Fourier Transform, sinyal echo ini dapat dianalisis dalam bentuk spektrum NMR dengan puncak spektrum menunjukkan frekuensi resonansinya. Diperoleh bahwa frekuensi resonansi akan menurun seiring dengan kenaikan temperatur. Posisi frekuensi pada temperatur 0 K adalah sebesar 85,41 MHz, hal ini memperlihatkan bahwa medan hyperfine dari Fe sebesar 2,14 T pada temperatur 0 K. Kurva antara frekuensi resonansi dengan temperatur menunjukkan bahwa magnetisasi tidak tepat sebanding dengan hukum Bloch T2 namun lebih cocok dengan bentuk persamaan eksponensial yang berkaitan dengan suatu gap energi yang berasal dari dispersi spin wave. Hal ini menguatkan bahwa bahan FeF3 merupakan bahan yang bersifat antiferromagnetik, namun bukan antiferromagnetik sederhana. Berdasarkan fitting, diperoleh gap energi sebesar 11,466 meV dan energi anisotropi sebesar 1,045 meV.